Psychosocial effects of a behavioural augmentation of existing public physical activity programs for middle-aged and older adults in Ireland. - Enrique García Bengoechea; Ciaran Doyle; Chloe Forte; Andrew O'Regan; Amanda M Clifford; Stephen Gallagher; Alan Donnelly; Liam Glynn; Andrew W Murphy; Ali Sheikhi; Catherine B Woods (PLoS ONE)
The combination of an ageing population, increasing prevalence of preventable noncommunicable diseases and a decline in physical activity with age emphasizes the need for investment in physical activity programs and services for older people. This study aimed to add to the initial evidence on the effectiveness of the Move for Life (MFL) intervention by examining its effects on psychosocial health outcomes and determinants of physical activity. MFL is an intervention that aims to augment existing community-based public physical activity programs for middle-aged and older adults in Ireland with strategies derived from behavioural theory and support from peer leaders. A 3-arm cluster randomised feasibility trial compared MFL intervention, usual provision (UP) and waiting list control (CON) groups at baseline (T0), post-intervention (T1, at 8-, 10- or 12-weeks) and 6-month follow up after baseline (T2). Psychosocial health and determinants of physical activity were assessed at each occasion by validated self-report measures. Linear or generalized linear mixed models were fitted to estimate group differences over time. Of 733 recruited individuals, 601 (mean age: 63.06 ± 8.1 years, 80.4% female) met study inclusion criteria. Significant advantages were found in the MFL group relative to UP in ratings of self-efficacy to overcome barriers to physical activity participation, subjective norms for and attitudes towards participation in physical activity (ps < .05). Subsequent analyses accounting for implementation fidelity revealed additional advantages for the 'high fidelity' MFL group relative to other groups, notably regarding loneliness and relatedness to others, perceived behavioural control, attitudes toward and intentions to participate in physical activity (ps < .05). The pattern of results shows the potential of MFL to impact positively the psychosocial health of inactive adults aged 50 + years and change psychosocial determinants of physical activity, particularly when implemented as intended. The results suggest as well that existing physical activity programs may have unexpected psychosocial consequences.